Service user involvement in pre-registration children's nursing education: the impact and influence on practice: a case study on the student perspective. (December 2013) - Rhodes, Christine Amanda
<x xml:space="preserve">Abstract</x> This article reports on a study that aimed to conduct an in-depth investigation into the impact of user involvement on student learning and subsequent influence on practice as a qualified nurse. This was undertaken through a single case study that followed a narrative inquiry approach. UK policy has recommended user involvement in healthcare education for a number of years; this has in turn increased requirements for involvement from Professional, Statutory and Regulatory Bodies. The Nursing and Midwifery Council (NMC, 2010) now requires program providers to clearly demonstrate how service users and carers contribute to program design, delivery and assessment. Although the literature base is expanding there remains limited evidence of the impact of involvement on student learning and improved outcomes for patients. Narratives were collected from a children's nursing student on completion of her 3-year nurse education program and again after practicing as a qualified children's nurse for 1 year. Taking part in the research enabled the participant to consider and reflect on her experience of user involvement in her education and training. Analysis followed an interpretive approach utilizing "The Listening Guide" (Doucet & Mauthner 2008) with the researcher's interpretation of how the experience was conveyed with clear acknowledgement of reflexivity.The findings identified central themes of authenticity, knowledge of self, resilience and coping, professional relationships, personalization of care, and influence on practice. This demonstrates transformative learning and support to practice, with preparation for situations and ideas on how to respond with empathy and compassion. This article contributes to the emerging evidence base specifically from a children's nursing perspective, an area with a dearth of published material. Further research with a range of students is required to explore the lasting impact on practice.